SISTEM INFORMASI AKUNTANSI DAN PEMECAHAN MASALAH PENGGAJIAN KARYAWAN BULANAN PADA CV KATHE BEAUTY STORE - Vivi Ade Rivani; Hwihanus Hwihanus (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study was made with the aim of finding out how to solve the problem of the payroll accounting system that was implemented by Kathe Beauty Store. Payroll is a form of direct reward offered to workers as payment for the work they have completed. Kathe Beauty Store is a cosmetic store in Surabaya. The research method used is descriptive qualitative method. Analysis of the data used in this research is by analyzing the relevant functions, supporting papers, accounting records used, network procedures, and assessing activities related to problem solving in terms of monthly employee payroll. In this case the payroll information system that is applied is still not in accordance with the accounting records because the greater a business activity is carried out, the more labor is needed. Thus causing problems in terms of managing the management of employee salaries. Then it is necessary to solve problems related to payroll information systems so that they can process data and produce the right information for making decisions. As well as to avoid all forms of possible errors that occur in the implementation of their respective responsibilities.